Some new construction methods of variance balanced block designs with repeated blocks - Ceranka, Bronisław (Metodološki zvezki, 2008)
Some new construction methods of the variance balanced block designs with repeated blocks are given. They are based on the specialized product of incidence matrices of the balanced incomplete block designs.
Keywords: Matematična statistika; Mathematical statistics; Blockmodeling; Bločno modeliranje; statistične metode; raziskave